2014
DOI: 10.1155/2014/945803
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Mouse Thymidylate Synthase in Tertiary Complex with dUMP and Raltitrexed Reveals N-Terminus Architecture and Two Different Active Site Conformations

Abstract: The crystal structure of mouse thymidylate synthase (mTS) in complex with substrate dUMP and antifolate inhibitor Raltitrexed is reported. The structure reveals, for the first time in the group of mammalian TS structures, a well-ordered segment of 13 N-terminal amino acids, whose ordered conformation is stabilized due to specific crystal packing. The structure consists of two homodimers, differing in conformation, one being more closed (dimer AB) and thus supporting tighter binding of ligands, and the other be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…The Ca RMSD values between the liganded and unliganded mTS structures presented here, as well as between these structures and the crystal structures of other ternary complexes with dUMP and Tomudex, including those with hTS [15,16], rTS [17] and mTS [18], are shown in Table 3. The superimposition of the mTS, mTS-dUMP and mTS-FdUMP-meTHF structures is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Ca RMSD values between the liganded and unliganded mTS structures presented here, as well as between these structures and the crystal structures of other ternary complexes with dUMP and Tomudex, including those with hTS [15,16], rTS [17] and mTS [18], are shown in Table 3. The superimposition of the mTS, mTS-dUMP and mTS-FdUMP-meTHF structures is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cavity in the dimer interface could serve as an allosteric site used to regulate the conformational switching between the active and inactive states [ 1 , 30 ]. In addition, TYMS performs at least two different functions with specific interaction regions: the dimer obligates catalytic function, while both the monomer and the dimer are believed to play crucial roles in TYMS–mRNA recognition and regulation [ 31 , 32 , 33 , 34 ]. In this study, we found TYMS not only formed a dimer, but also an octamer by intermolecular Cys43-disulfide ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cavity in the dimer interface could serve as an allosteric site of to regulate the conformational switching between the active and inactive states [1,30]. In addition, TYMS performs at least two different functions with specific interaction regions: dimer obligates catalytic function, while both the monomer and dimer are believed to play a crucial role in TYMS-mRNA recognition and regulation [31][32][33][34]. In this study, we found TYMS not only formed dimer, but also octamer by intermolecular Cys43-disulfide ( Figure 3).…”
Section: Analysis Of Kinetic Properties Of All Oligomeric Formsmentioning
confidence: 99%